Environmental and social Impacts from palm based biofuel development in Indonesia - Andriani, R.; Andrianto, A.; Komarudin, Heru; Obidzinski, K. (2011)
This paper reviews oil palm biofuel development and analyzes social and environmental impacts of oil palm plantations in Indonesia. Three plantation study sites were selected in West Papua (Manokwari), West Kalimantan (Kubu Raya) and Papua (Boven Digoel) and used as case studies to illustrate likely impacts of biofuel plantations. These plantations are being developed or expanded in the aftermath of the 2006 National Energy Policy and managed by companies with supply connections to biodiesel industry. Household surveys, focus group discussions, and key informant interviews were employed to gauge respondent perceptions about social, economic and environmental impacts. Concurrently, spatial analysis was used to assess the changes in forest cover. The development of oil palm in all three sites has caused deforestation and is likely to lead to further loss of forest as expansion continue to take place. Some communities did enjoy economic and social benefits from oil palm plantations such as more stable and reliable income, road access, better healthcare services. In Kubu Raya, some communities benefited both from employment opportunities and from sales of smallholder oil palm harvests. In Kubu Raya and Boven Digoel sites, some indigenous communities and migrants developed good inter-ethnic relations, although this was not the case in Manokwari. Other communities experienced increasing restrictions on traditional land use rights and outright land losses. Conflicts over land between indigenous communities and oil palm companies were observed in all three sites. Communities in all three sites experienced additional adverse environmental effects such as water pollution and flooding. The findings call for plantation policy makers to revisit the principles governing largescale land allocation for plantations. They need to pay particular attention to whether and to what extent the free, prior, and informed consent principle is being applied during the land acquisition process. The smallholder and nucleus oil palm schemes need improvements in efficiency and profitability. Finally, stringent sanctions are needed against companies failing to implement legally binding environmental monitoring and management plans.